Natural disturbances and masting: from mechanisms to fitness consequences. (6th December 2021) - Vacchiano, Giorgio; Pesendorfer, Mario B.; Conedera, Marco; Gratzer, Georg; Rossi, Lorenzo; Ascoli, Davide
Abstract : The timing of seed production and release is highly relevant for successful plant reproduction. Ecological disturbances, if synchronized with reproductive effort, can increase the chances of seeds and seedlings to germinate and establish. This can be especially true under variable and synchronous seed production (masting). Several observational studies have reported worldwide evidence for co-occurrence of disturbances and seed bumper crops in forests. Here, we review the evidence for interaction between disturbances and masting in global plant communities; we highlight feedbacks between these two ecological processes and posit an evolutionary pathway leading to the selection of traits that allow trees to synchronize seed crops with disturbances. Finally, we highlight relevant questions to be tested on the functional and evolutionary relationship between disturbances and masting. This article is part of the theme issue 'The ecology and evolution of synchronized seed production in plants'.